2020
DOI: 10.3389/fpsyg.2020.00269
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Structural Integration Mediate the Impact of Metacognition on Functioning in Non-affective Psychosis: Adding a Psychodynamic Perspective to the Metacognitive Approach

Abstract: Synthetic metacognition is defined by integrative and contextualizing processes of discrete reflexive moments. These processes are supposed to be needed to meet intrapsychic as well as interpersonal challenges and to meaningfully include psychotic experience in a personal life narrative. A substantial body of evidence has linked this phenomenon to psychosocial functioning and treatment options were developed. The concept of synthetic metacognition, measured with the Metacognition Assessment Scale-Abbreviated (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 92 publications
1
4
0
Order By: Relevance
“…Thus, people with structural impairments may have greater difficulties in regulating themselves and their relationships to others in stressful situations, which makes them more prone to burnout. These results are in line with previous studies that found positive correlations between structural impairment and various mental problems in general (Mestel et al, 2004;Benecke et al, 2009Benecke et al, , 2018Ehrenthal et al, 2012;Obbarius et al, 2019;Baie et al, 2020;Bröcker et al, 2020) and burnout in particular (Bugaj et al, 2016). A concept that is close to structural impairment is emotional intelligence (Jauk and Ehrenthal, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, people with structural impairments may have greater difficulties in regulating themselves and their relationships to others in stressful situations, which makes them more prone to burnout. These results are in line with previous studies that found positive correlations between structural impairment and various mental problems in general (Mestel et al, 2004;Benecke et al, 2009Benecke et al, , 2018Ehrenthal et al, 2012;Obbarius et al, 2019;Baie et al, 2020;Bröcker et al, 2020) and burnout in particular (Bugaj et al, 2016). A concept that is close to structural impairment is emotional intelligence (Jauk and Ehrenthal, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…This, in turn, can lead to a reduced ability to regulate internal and external states of tension, which makes it difficult to cope with developmental tasks and stressful situations later in life (OPD Task Force, 2011;Bugaj et al, 2016). In general, previous research found that people with structural impairments are prone to various mental illnesses (Grande et al, 1998;Mestel et al, 2004;Benecke et al, 2009Benecke et al, , 2018Ehrenthal et al, 2012;Obbarius et al, 2019;Baie et al, 2020;Bröcker et al, 2020). Furthermore, it has been shown that structural impairment is higher in patients with a personality disorder than in patients without a personality disorder (Benecke et al, 2009;Ehrenthal et al, 2012).…”
Section: Self Objectmentioning
confidence: 95%
“…Next to mentalizing impairments (see Fett, Viechtbauer, Penn, van Os, & Krabbendam, 2011 for an overview), impaired metacognition, a construct largely overlapping with mentalization, has also been identified as a major contributor to social dysfunction (e.g. see Arnon-Ribenfeld, Hasson-Ohayon, Lavidor, Atzil-Slonim, & Lysaker, 2017 for an overview; Gagen, Zalzala, Hochheiser, Martin, & Lysaker, 2019 ; Bröcker et al, 2020 ), particularly deficits in specific sub-components of meta-cognition such as empathic perspective taking and self-reflectivity (see Brüne, Dimaggio, and Lysaker, 2011 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Making sense of FEP was shown to be important both prior to seeking help from a service and afterwards, and work is needed to understand how it can be best addressed within services. With psychotherapeutic interventions for voice-hearing, it may be beneficial to include interventions such as meta-cognition , narrative insight, and rapport-building, as research has demonstrated improved outcomes (Bröcker et al, 2020;Eichner & Berna, 2016;Lopez-Morinigo et al, 2020;Moritz et al, 2019;Rosenbaum et al, 2012).…”
Section: Psychotherapeutic Approaches Within Servicesmentioning
confidence: 99%